Analysis of development planning of own use gas pipeline from gas compressor stations to gathering stations in X field / Muhammad Ariyon, Muhammad Setriya Ramadhan - Ariyon, Muhammad; Ramadhan, Muhammad Setriya (Universiti Teknologi MARA, Sarawak, 2023)
Trunkline gas network system from Gas Compressor Station (GCS) B to GS.B-GS.B5 has a total distance of 18 km. The distance of GS.B4-GS.B5 is 9400 m. Gas is the main fuel for engines at gathering stations. A deadlock was found on the GS.B4-GS.B5 pipeline. The solution to this problem is to plan a pipeline between GS.B4-GS.B5 for optimal gas supply. This study conducted an economic analysis of the planning of pipe construction with the same trunkline diameter. The diameter was selected by looking at the effect of pressure drop and erosional velocity using the Pipesim. Then, a problem-solving approach was taken by building a system using a pig launcher. Based on the research results, in the existing conditions with a distance of 9400 m using a diameter of 6 and 4 inches, there is a high pressure drop. Scenario planning minimizes pressure drop by using equal diameter pipes of 4, 6 and 8 inches. The analysis results show that the selected diameter is 6 inches. Pig launcher is designed with safe specs and design. Calculation of the project's economic indicators with an investment of 505,911 US$M and an oil price of 62.38 US$/bbl.